Digital Radiography Using Digital Detector Arrays Fulfills Critical Applications for Offshore Pipelines. (2nd June 2010) - Moreira Moreira, Edson Vasques Edson Vasques; Barbosa Rabello Barbosa Rabello, José Maurício José Maurício; Pereira Pereira, Marcelo dos Santos Marcelo dos Santos; Lopes Lopes, Ricardo Tadeu Ricardo Tadeu; Zscherpel Zscherpel, Uwe Uwe
Abstract : Digital radiography in the inspection of welded pipes to be installed under deep water offshore gas and oil pipelines, like a presalt in Brazil, in the paper has been investigated. The aim is to use digital radiography for nondestructive testing of welds as it is already in use in the medical, aerospace, security, automotive, and petrochemical sectors. Among the current options, the DDA (Digital Detector Array) is considered as one of the best solutions to replace industrial films, as well as to increase the sensitivity to reduce the inspection cycle time. This paper shows the results of this new technique, comparing it to radiography with industrial films systems. In this paper, 20 test specimens of longitudinal welded pipe joints, specially prepared with artificial defects like cracks, lack of fusion, lack of penetration, and porosities and slag inclusions with varying dimensions and in 06 different base metal wall thicknesses, were tested and a comparison of the techniques was made. These experiments verified the purposed rules for parameter definitions and selections to control the required digital radiographic image quality as described in the draft international standard ISO/DIS 10893-7. This draft is first standard establishing the parameters for digital radiography on weld seam of welded steel pipes for pressure purposes to be used on gas and oil pipelines.